Peran Vitamin D Dalam Menurunkan Risiko Penyakit Kardiovaskular - Lim, Audi; Arsita, Elli (Universitas Kristen Krida Wacana, 2024)
Cardiovascular disease is the main cause of death in the world. Vitamin D is known to have an influence on the cardiovascular system through the role of the vitamin D receptor (VDR) expressed by vascular endothelial smooth muscle cells and cardiomyocytes. This literature review analyze the role of vitamin D in relation to the risk of cardiovascular disease through a study of scientific articles from Google Scholar and Pubmed. The results showed that patients with severe vitamin D deficiency (serum 25(OH) levels <10 ng/ml) had an increased risk of myocardial infarction with OR 4.5 (95% CI 2.2–9.2), and increased risk of PAD with OR 3.872 (95% CI: 1.168–12.841), while vitamin D deficiency (serum 25(OH) levels <20 ng/ml) caused an increased risk of acute ischemic stroke with OR 16.64 (95% CI: 5 .66–42.92; p < 0.001). Administration of 1x 600,000IU or 2x300,000IU intramuscular vitamin D in coronary heart disease patients with deficiency showed significant reduction in the inflammatory marker hsCRP and improved endothelial function. However, in clinical trials, significant but inconsistent results were obtained due to differences in the cut off value for Vit D deficiency, diversity in age, gender, variations in polymorphisms, smoking habits, physical activity, body weight, and various comorbidities suffered by patients.